Outcomes of Congenital Cataract Surgery in a Tertiary Care Hospital - Saliha Naz, Kanwal Latif, Munira Shakir, Shakir Zafar, Syed Fawad Rizvi (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine outcomes of congenital cataract surgery in a tertiary care hospital. Material and Methods: A total of 192 eyes of 120 patients of age group 3-8 years with visually significant congenital cataract (? 3 mm in diameter) underwent cataract surgery with posterior chamber foldable intraocular lens implantation were enrolled in this interventional study. Posterior capsulotomy with anterior vitrectomy was performed in all cases. The span of study was July 2011 to January 2013. The minimum follow up of patients was 6 months. In follow-up period postoperative treatment, management of surgical complications, amblyopia therapy and assessment of visual acuity was done. Final outcome of congenital cataract surgery in terms of improvement in visual acuity was assessed at the end of 6th month. The study was performed at Layton Rehmatullah Benevolent Trust Eye Hospital, Karachi. Results: At the end of study 51% of patients achieved good vision and the better visual outcome is significantly higher in younger age groups. Fibrinous reaction was the most common complication occurred in this study. Conclusion: This study demonstrate that early congenital cataract surgery is a safe procedure and beneficial in achieving good visual acuity.